Ustvarjanje pravljice - Fric, Tinka (Šolska knjižnica, 2017)
Implementing library and information knowledge in a library offers a wide range of opportunities. One of them is the introduction of elements of formative assessment, through which students become more actively involved in lessons. Library and information knowledge is most often implemented in the form of cross-curricular collaboration. In this lesson it was linked to a Slovenian Language lesson in the 4th grade. Students revised their knowledge of folk tales and literary fairy tales, integrated it with their knowledge about the library, became familiar with the library%s layout and used library services, after which they independently created their own fairy tale as evidence of learning. The students were active and motivated for work.
Keywords: formativno spremljanje; knjižnično informacijsko znanje; medpredmetno povezovanje; osnovne šole; povratne informacije; pravljice; preverjanje znanja; samovrednotenje; slovenščina; šolske knjižnice